Field Work Practice Management - Sitti Rachma Abu; Roos MS Tuerah; Viktory NJ Rotty (International Journal on Integrated Education, 2022)
This study aims to determine how the management of practice in SMK Negeri 1 Amurang. This research is a descriptive study, with the research respondents being principals, vice principals, teacher administration. The data collection method used by the researcher is using interviews and research using an interview and documentation approach. Data that has been obtained from interviews with informants. To know the organization, implementation, planning, and evaluation. From the research results obtained indicate that the management of the implementation of the Field Work Practice (PKL) at SMK Negeri 1 Amurang if viewed from the organization canrunning well indicated by the existence of the organizational structure of street vendors and the division of tasks board, the implementation went well. Most of the students stated that they were good in terms of planning. Based on the conclusions of the study, it is recommended thatthe learning process in schools can be fulfilled properly so that in the implementation of Field Work Practices (PKL) students can apply the knowledge gained at school by going directly into the world of DU/DI work.